East Indian temple, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Photo of mosque in San Fernando, Trinidad and Tobago. No. 25557.
Colour: White, Grey and Green Hues; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Churches--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Religious institutions--Trinidad and Tobago